Leveraging innovation knowledge management to create positional advantage in agricultural value chains; Aprovechando la gestión del conocimiento de la innovación para crear ventaja posicional en las cadenas de valor agrícola - Khanh Le Phi Ho; Chau Ngoc Nguyen; Rajendra Prasad Adhikari; Morgan P. Miles; Lawrence Bonney (Journal of Innovation & Knowledge (JIK), 2019)
This study employs resource advantage theory to identify how beef cattle value chain actors' resources are translated into the positional advantage and how that then affects their financial performance in an emerging country context. The study tested was designed to understand if: (1) the resources of beef cattle value chain actors are positively related to positional advantage; and (2) positional advantage is positively related to the financial performance of the actors within the value chain. The unit of analysis in this study is a single beef cattle value chain. One hundred and ninety value chain actors were interviewed and the findings appear to indicate that chain actors' resources are an antecedent to positional advantage in the marketplace and that this market advantage is an antecedent to the superior financial performance of beef cattle value chain
Keywords: M3; Q1; P3; 650; Diferenciación; Differentiation; Innovación; Innovation; Low-cost advantage; Market orientation; Orientación al mercado; Positional advantage; Ventaja de bajo costo; Ventaja posicional